Eosinophils and mast cells in chronic gastritis: possible implications in carcinogenesis - Piazuelo, M. Blanca; Camargo, M. Constanza; Mera, Robertino M.; Delgado, Alberto G.; Peek, Richard M.; Correa, Hernan; Schneider, Barbara G.; Sicinschi, Liviu A.; Mora, Yolanda; Bravo, Luis E.; Correa, Pelayo (Human pathology, 2008)
Eosinophils and mast cells participate in the immune response against Helicobacter pylori, but their involvement in the gastric precancerous process is unclear. This study aimed to estimate eosinophil and mast cell density in antral mucosa in subjects from 2 Colombian populations with contrasting gastric cancer risks. Gastric mucosa biopsies were collected from 117 adult males (72 from a high-risk area and 45 from a low-risk area). A histopathology score was used to quantify severity of the lesions. Quantitation of eosinophils in hematoxylin-eosin–stained sections and mast cells in immunostained sections for CD117/c-Kit was performed. Helicobacter pylori infection and genotyping were assessed in Steiner stain and polymerase chain reaction, respectively. Logistic regression models and semiparametric cubic smoothing splines were used for analysis of the results. Eosinophil density was significantly higher in subjects from the low-risk area as compared with subjects from the high-risk area. In both populations, eosinophil density increased with the histopathology score in the progression of lesions from normal morphology to multifocal atrophic gastritis. Intestinal metaplasia and dysplasia specimens showed further increase in eosinophil density in the high-risk area but an abrupt decrease in the low-risk area. Mast cell density increased in parallel to the histopathology score in both populations. Our results suggest that eosinophils play a dual role in chronic gastritis. In the low-risk area, elevated eosinophil density represents a T helper 2–biased response that may down-regulate the effects of proinflammatory cytokines preventing cancer development. In contrast, in the high-risk area, eosinophils might promote a T helper 1–type response leading to progression of precancerous lesions.